The effect of exercise on prescription on physical activity and wellbeing in a multi-ethnic female population: A controlled trial - Gademan Maaike GJ; Deutekom Marije; Hosper Karen; Stronks Karien (BMC, 2012)
Abstract Background In Western countries, individuals from multi-ethnic disadvantaged populations are less physically active than the Western population as a whole. This lack of physical activity (PA) may be one of the factors explaining disparities in health. Exercise on Prescription" (EoP), is an exercise program to which persons are referred by primary care. It has been developed to suit the needs of physically inactive women from diverse ethnic backgrounds living in deprived neighborhoods in the Netherlands. The effectiveness of this program has however, not yet been proven. Methods A total of 514 women from diverse ethnic backgrounds were included in this study (192 EoP, 322 control group). Women in the EoP group participated in 18 sessions of supervised PA. The control group received care as usual. At baseline, 6 and 12 months the women attended an interview and a physical examination. Outcome measures were PA, BMI, weight circumference, fat percentage, oxygen uptake, mental well-being, subjective health and use of care. Results Of the participants 59% had a low educational level and 90% of the women were overweight or obese. Compliance was high, only 14% dropped out during the course of the program. Total PA did not change, PA during leisure time increased at 6 and at 12 months and PA during household activities increased at 12 months (PEoPvsControl < 0.05). EoP had no significant effect on the other outcome variables. Conclusions EoP was successful in recruiting its target population and compliance was high. The effect of EoP on PA, health and mental well-being was limited. In this format EoP does not seem to be effective for increasing PA and the health status of non-Western migrant women. Trial registration Dutch Trial register: NTR1294